A cryopreserved sperm repository strategy for WorldFish genetically improved carp - Bodenstein, Sarah; Tiersch, Terrence; Reza Hossain, Mostafa Ali; Hamilton, Matthew; Yeasin, Mohammed; Akhter, Md; Trinh, Trong; Mahmuddin, Mahirah (WorldFish, 2023)
This report identifies key stakeholders and pathways for the use of cryopreserved sperm repository technology for carp genetic improvement and dissemination in Bangladesh. Relationship mapping has been used to delineate relationships among suppliers, producers, and customers and their facilities.